2014
DOI: 10.5296/jsss.v2i1.6284
|View full text |Cite
|
Sign up to set email alerts
|

Iranian Women’s Identity and Cyberspace: Case study of Stealthy Freedom

Abstract: Gender related identity formation of women has been influenced by numerous parameters in recent years. The status of women in Iran today is not comparable to that in the past. Significant changes have occurred as communities and households respond to social and economic shifts associated with globalization, new technologies and environmental pressures. What is obvious is that, along with the globalization and current social and intellectual upheavals, society and women both have adopted a more transitory and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…As mentioned above, "My Stealthy Freedom" was created in 2014 by an England-based journalist from the Iranian diaspora, and has since then received over 924,000 "likes," becoming a hot issue both in and out of Iran. By addressing the lack of "freedom of choice" regarding the hijab policy, it has gained the attention of many Iranian researchers (Hamzehei 2014;Karimi 2014;Khiabany 2015;Koo 2014;Lewis 2015;Novak & Khazraee 2014;Sreberny 2015).…”
Section: An Ethnographic Analysis Of "My Stealthy Freedom"mentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, "My Stealthy Freedom" was created in 2014 by an England-based journalist from the Iranian diaspora, and has since then received over 924,000 "likes," becoming a hot issue both in and out of Iran. By addressing the lack of "freedom of choice" regarding the hijab policy, it has gained the attention of many Iranian researchers (Hamzehei 2014;Karimi 2014;Khiabany 2015;Koo 2014;Lewis 2015;Novak & Khazraee 2014;Sreberny 2015).…”
Section: An Ethnographic Analysis Of "My Stealthy Freedom"mentioning
confidence: 99%
“…In particular, I analyze the Facebook page "My Stealthy Freedom," where women post pictures of themselves without their hijabs and share their stories. Although "My Stealthy Freedom" has been gaining much notoriety in the press and academia (Hamzehei 2014;Karimi 2014;Khiabany 2015;Koo 2014;Lewis 2015;Novak & Khazraee 2014;Sreberny 2015), the voices of women as subjects has been missing in these studies. It is this void which I seek to fill, by connecting women's online participation with developments in the offline social movements in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…It has been perceived that Muslim women are affected by the constraints in society and by stereotypes that are difficult to change even if this change is sought after only in the virtual space where the Muslim women have the opportunity to manage their self-representation the way they want. In his study, Karimi (2014) concluded that new media offer decent promises for Muslim women to construct their identities of their own in the public sphere. Muslim women have gradually risen from their traditional roles of being just mothers and housewives confined mainly to the private spheres of their families to become influential players in public life.…”
Section: Problem Statementmentioning
confidence: 99%
“…Moreover, there are many other photographs on the page depicting women from behind, so that their face cannot be recognized by anybody. The "peasant resistance" on these Facebook pages challenges the optimistic perception of the movement by the public, the media (Saul, 2015;Threadgould, 2015), academics (Karimi, 2015;Koo, 2014;Novak & Khazraee, 2014), and the activists themselves. In such a setting, the online public sphere has led to the creation of a comfortable space to voice dissent, yet maybe so comfortable that all movements have remained limited to the boundaries of the online, virtual world.…”
Section: Illusion Of Resistancementioning
confidence: 99%
“…However, in recent years, due to the higher accessibility and popularity of social networking websites, such as Facebook, some Iranian women have formed a movement against compulsory hijab in Iran (Karimi, 2015;Saul, 2015;Threadgould, 2015). Although social networks such as Facebook and Twitter are filtered in the country, citizens often bypass the censorship barriers with different means.…”
mentioning
confidence: 99%